The Effects of Pretreatment with Different Concentrations of Sodium Hydroxide on Paddy Straw for Biogas Production - Tuan Yusof, Tengku Roslina; A/L N Gopal, Thinesh Raj (Advanced and Sustainable Technologies (ASET), 2026)
Paddy straw is an abundant agricultural residue with high potential for renewable energy generation through anaerobic digestion; however, its lignocellulosic structure limits biodegradability and biogas yield. This study evaluates the effect of sodium hydroxide (NaOH) pretreatment on biogas production from fresh and dried paddy straw at concentrations ranging from 0% to 10% (w/v). The straw was immersed in NaOH solutions for 24 hours and subsequently digested under mesophilic conditions (35 °C) for 17 days in batch reactors. Biogas production was monitored daily, and cumulative yields were recorded. The results indicate that biogas production is higher in the treated sample than in to untreated sample. The treated sample shows that optimal concentrations are 6% NaOH for fresh paddy straw (65.8 mL cumulative yield) and 8% NaOH for dried paddy straw (52.05 mL). Excessive alkalinity negatively affected microbial activity and reduced performance. These findings demonstrate that optimized NaOH pretreatment improves digestibility and biogas yield, with substrate condition playing a critical role in determining optimal treatment levels, and align with SDG 7 (Affordable and Clean Energy) and SDG 12 (Responsible Consumption and Production).